The figure of bishop Hryhorii Khomyshyn in contemporary Polish historiography - Klish, Andriy; Pryidun, Stepan (Вісник гуманітарних наук, 2025)
The article analyzes the interpretations of Bishop Hryhorii Khomyshyn in contemporary Polish historiography. Based on the works of leading Polish scholars, it explores the principal approaches to understanding the ideological legacy and socio-ecclesiastical activity of the Stanislaviv bishop. Special attention is given to the issues of Latinization of the Greek Catholic Church, Khomyshyn’s polemic against radical forms of Ukrainian nationalism, and his efforts toward interconfessional understanding and Polish-Ukrainian reconciliation. The article highlights the growing interest among Polish researchers in the bishop’s spiritual and moral heritage as a source of interethnic dialogue and religious renewal. The study concludes that Khomyshyn is perceived in Polish historiography as a symbol of Christian ethics, intellectual courage, and cultural resistance to radicalism.